Penetration of Dutch Colonial Power Against the Sultanate of Jambi, 1615-1904 - Budi Purnomo (Diponegoro University, 2020)
The arrival of the Dutch in Jambi gave the impression of almost coincidence because Jambi was not familiar and not a large sultanate in Sumatra compared to Aceh. Even Jambi as a relatively small and unimportant kingdom in the 19th century. However, during the colonial era, some penetrations made to the Sultanate of Jambi. This study examines several factors that caused resistance from the rulers and local people of Jambi against the Dutch colonial power. By using a historical method that emphasized on the secondary sources, this study identifies those factors to make penetration. It shows that economic factors in which the Dutch monopoly trading system is not acceptable to the rulers and local people. It is detrimental and contrary to freedom of trade. Meanwhile, colonial expansion is contrary to the ethical principles they profess. In addition, the failure of the Jambi sultanate had the weakness of their political institutions in facing Dutch colonial penetration. The weakness of their political institutions is influenced by the poor main foundation of the empire and the values of the royal tradition.